Pengaruh Degradasi Pelumas Bekas Menggunakan Katalis Zno/Zeolit terhadap Kandungan Mg dan Na secara Fotolisis - Zilfa, Z.; Yusuf, Yulizar; Hanifah Adhisa (Departemen Kimia Universitas Andalas, 2025)
Every year the number of car users has increased significantly, leading to an increase in used lubricant waste. Used lubricants are the result of oil that has been subjected to engine friction, combustion residue and dust. As a result, the effectiveness of the lubricant decreases, and if left for a long time, these contaminants can turn into harmful abrasive particles. The purpose of this study is to see the effect of using ZnO/Zeolite catalysts in degrading used lubricants on the reduction of Mg and Na content by photolysis. Analysis of Mg and Na metal content in used lubricants was carried out using Atomic Absorption Spectrophotometry (AAS). The results of this study showed that the degradation process through photolysis lasted for 15 minutes with the utilization of 0.4 grams of ZnO/Zeolite, and the volume of used lubricant samples was 10 mL for Mg and Na metals. After the degradation process was carried out under optimal conditions, the percentage of metal degradation of Mg reached 84.407% and Na 78.155%. Analysis of used lubricants before and after the degradation process was carried out using FTIR and UV-Vis Spectrophotometer, which showed a change in the spectrum, characterized by a shift in wave numbers, which indicated that the degradation had been successfully carried out. The results of catalyst characterization using FTIR and XRD showed that there was no change in the structure of ZnO/zeolite.